DEVELOPMENT OF AN ANDROID-BASED SERENITY MEDITATION GUIDE FOR TEENS - Sugianto, Sugianto; Wisetia, Adinda; Loka, Eka Hita; Angel, Metta Cris (Jurnal Pencerahan, 2023)
The problem in this study is that there is no an android-based serenity meditation guide for teenager. The aims of this research is to develop an android-based serenity meditation guide for teenager. The method used in this research is Research and Development (R&D) with the Analyze, Design, Development, Implementation, and Evaluation (ADDIE) development model. Data collection techniques use questionnaires and interviews. Data collection instruments use questionnaires (grids), interview guidelines, and instrument validity sheets. The data validity technique has been validated by experts. The data analysis technique uses Gregory analysis. The results of this study are TAPA-KU can be used as a meditation guide, users can use this application interested in serenity meditation by using the TAPA-KU application. Teenagers need calm meditation as coping with stress with the help of the TAPA-KU application. The TAPA-KU application meets the standards and is fairly good because the construct validation value is > 0.75, and the TAPA-KU application as a whole gets a score of 86.65%.